Uji Kadar Total Tanin dari Ekstrak Daun Sembung (Blumea balsamifera) serta Toksisitasnya Dengan mentode BSLT - Pranata, Guswarni; Indriaty, Indriaty; S. Pandia, Ekariana (Green Publisher Indonesia, 2025)
Blumea balsamifera is one of the Asteraceae family known as Sembung leaves. B. balsamifera is often used in traditional medicine. This study aims to evaluate the potential biological activity of Sembung leaves (Blumea balsamifera) through the determination of total tannin levels and toxicity tests using the Brine Shrimp Lethality Test (BSLT) method. Leaf extraction is carried out by the maceration method using methanol solvent. The total tannin content was determined using the colorimetric method with the Folin-Ciocalteu reagent, resulting in a tannin content of 358.04 mg TAE/g of extract. The toxicity test showed an LC50 value of 56.58 μg/mL, which indicated that the methanol extract of B. balsamifera leaves was toxic. These results suggest that the high tannin content correlates with the toxicity properties of the extract, which has the potential to be further developed as a therapeutic agent.